How can I help you? Multiple resource availability promotes generosity with low-value (but not high-value) resources. (August 2021) - Harrell, Ashley
People commonly possess multiple, differentially-valued resources they can use to benefit those in need: contributing money, volunteering time, donating unwanted possessions, posting on social media to raise awareness, and more. But the majority of experimental work on generosity and helping behavior has studied giving when only a single valuable resource is available to give. This project considers: when people have multiple, differentially-valued resources to use to benefit a dependent other, which resources will they use to help, and how much? Results from an experiment show, first, that generosity is higher with lower-value resources. More importantly, when multiple, differentially-valued resources are available to use to benefit others, helping is higher than when a single resource is available, all else being equal. This is because when multiple resources are available, people are especially willing to give away their relatively lower-value resources. Put differently, when people can benefit others using multiple resources, they are more likely to consider how they should help, rather than whether they should.